Konsep Dialetika Penafsiran al-Qur’an: Tekstual, Kontekstual, dan Deradikalisasi - Esti Oktavya; Fatira Wahidah; Muh. Ikhsan; Nurdin (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the concept of dialectical interpretation of the Qur'an. This study uses a qualitative approach by applying the descriptive-analytical method. The results and discussion of this study indicate that the dialectical process of interpreting the Koran that makes the meaning of the Koran come alive requires a set of approaches, such as a textual approach, a contextual approach, and a deradicalization approach to the interpretation of the Koran. This study concludes that the dialectical concept of interpreting the Qur'an is the understanding or argument of several individuals about the science concerned with the Qur'an and its contents which are not understood and have vague meanings for the needs of Muslims. This study recommends the Qur'anic study institutes and interpretations to develop a dialectical interpretation methodology of the Qur'an.